Experimental study on the use of wood pellet briquettes in rocket stoves for household energy needs - Rafki Irianto; Yolli Fernanda; Primawati Primawati; Dori Yuvenda (Researcher and Lecturer Society, 2026)
This experimental study investigates the effect of air supply configurations on the combustion performance and thermal efficiency of wood pellet briquettes in rocket stoves for household energy use. With increasing global demand for energy and the depletion of fossil fuels, the shift to renewable biomass fuels, such as wood pellets, is essential to reduce carbon emissions and enhance energy efficiency. The study evaluates four airflow configurations: right fan only (F3), lower-left + right fans (F2+F3), two left fans (F1+F2), and all fans (F1+F2+F3). The results show that the F3 configuration achieved the fastest boiling time, highest boiling temperature, and lowest heat-loss temperature, indicating superior thermal performance. In contrast, configurations with higher airflow (F1+F2 and all fans) led to greater heat losses and slower boiling times, suggesting that excessive airflow can negatively affect efficiency. Additionally, the analysis of residual mass revealed that F3 and F2+F3 configurations produced the lowest residuals, indicating more complete combustion. This study provides important insights into optimising airflow configurations to improve the efficiency of biomass stoves. The findings offer practical implications for the design and operation of sustainable cooking technologies, promoting energy efficiency and reducing reliance on fossil fuels in households, particularly in rural areas.